An Fc?RIIa-binding peptide that mimics the interaction between Fc?RIIa and IgG - Cendron, A.; Wines, B.; Brownlee, R.; Ramsland, Paul; Pietersz, G.; Hogarth, P. (2008)
A disulphide-constrained peptide that binds to the low affinity Fc receptor, Fc?RIIa (CD32) has been identified and its structure solved by NMR. Linear (7-mer and 12-mer) and disulphide-constrained (7-mer) phage display peptide libraries were panned on recombinant soluble Fc?RIIa genetically fused to HSA (HSA-Fc?RIIa). Peptides were isolated only from the constrained peptide library and these contained the consensus sequence, CWPGWxxC. Phage clones displaying variants of the peptide consensus sequence bound to Fc?RIIa and the strongest binding clone C7C1 (CWPGWDLNC) competed with IgG for binding to Fc?RIIa and was inhibited from binding to Fc?RIIa by the Fc?RIIa-blocking antibody, IV.3, suggesting that C7C1 and IgG share related binding sites on Fc?RIIa. A synthetic disulphide-constrained peptide, pep-C7C1 bound to Fc?RIIa by biosensor analysis, albeit with low affinity (KD ~ 100 µM). It was significant that the Fc?RIIa consensus peptide sequence contained a Proline (Pro3), which when substituted with alanine abrogated Fc?RIIa binding, consistent with Pro3 contributing to receptor binding. Upon binding of IgG and IgE to their respective Fc receptors (Fc?Rs and FceRI) Pro329 in the Fc makes a critical interaction with two highly conserved Trp residues (Trp90 and Trp113) of the FcRs. The NMR structure of pep-C7C1 revealed a stabilizing type II ß-turn between Trp2 and Trp5, with Pro3 solvent exposed. Modelling of the pep-C7C1 structure in complex with Fc?RIIa suggests that Pro3 of C7C1 binds to Fc?RIIa by inserting between Trp90 and Trp113 of Fc?RIIa thereby mimicking the molecular interaction made between Fc?RIIa and IgG. © 2007 Elsevier Ltd. All rights reserved.